Influence of Media Staff Welfare on Effective Journalism Practice in Nigeria - Ifeanyi Nwokeocha (Jurnal Multidisiplin Madani, 2023)
An abstract is written along 100-200 words with a single space. Abstract content must explain the subject matter discussed in the article, the method used, the results or findings and conclusions. Abstracts are written in only one paragra This study examined the influence of media staff welfare on effective journalism. The study explore how media staff especially journalists’ welfare are poorly handled by media owners and managers, therefore hampering their effective practice of the profession. The study reviewed scholar’s opinion and empirical studies. Abraham Maslow Hierarchy of needs theory and functional/Efficiency theory were also used as the theoretical fame work of this study. The study recommended that media ownership managers should at fulfilling their duties which is to motivate journalists through good and attractive welfare packages; this is because it could encourage and drive them to stay on the side of truth, objective news, reporting, and fairness and give them courage to practice investigative journalism even in the face of intimidation and attacks; good working condition should be provided for journalists. It is also important that hard working staff are appreciated for their work etc